EYS, encoding an ortholog of Drosophila spacemaker, is mutated in autosomal recessive retinitis pigmentosa. - El-Aziz, A; Barragan, I; O'Driscoll, C; Goodstadt, L; Prigmore, E; Borrego, S; Mena, M; Pieras, J; El-Ashry, M; Safieh, L; Shah, A; Cheetham, M; et al. (2008)
Using a positional cloning approach supported by comparative genomics, we have identified a previously unreported gene, EYS, at the RP25 locus on chromosome 6q12 commonly mutated in autosomal recessive retinitis pigmentosa. Spanning over 2 Mb, this is the largest eye-specific gene identified so far. EYS is independently disrupted in four other mammalian lineages, including that of rodents, but is well conserved from Drosophila to man and is likely to have a role in the modeling of retinal architecture.